Jessica Rabbit : XERIOUS business - Wolf, Gary K. (Gary K. Wolf, 2022)
The gorgeous Toon superstar the whole world now knows as Jessica Rabbit started out in life as Jessica Krupnick, an ordinary young woman living in an all-too-human Toon-less world. Jessica trudges listlessly through day after day of drudgery, boredom, and disappointment. She knows in her heart that she's better than this. She's capable of doing so much more. She fantasizes being one of the secret agents in the books she reads every night to take her mind off her miseries. She imagines herself living a life of excitement, danger and action. Then one day she spots a mysterious want ad looking for "a woman seeking adventure." Through a combination of skill, cunning, and crafty derring-do, Jessica beats out all the other applicants. She wins her dream job. After two years of intense training, she becomes a glamorous and deadly agent of XERIOUS, a super-secret organization dedicated to pursuing and apprehending Criminal Masterminds.